Structural, elastic, thermo-physical and gamma radiation shielding efficiency of MnO2 doped TeO2-PbO-ZnO glasses - Alazoumi, S.H.; Umar, S.A.; Ahmad, A.F.; Sidek, H.A.A.; A. Awshah, Abdulbaset; Thakur, S.; Geidam, I.G. (Elsevier, 2024)
This paper presents the fabrication of glasses with chemical formula [(TeO2)0.70 – (ZnO)0.22 – (PbO)0.08] 1-x (MnO2)x where x = 0.02, 0.04, 0.06, 0.08 and 0.1 using melt quenching technique. The main objective is to explore the structural, elastic and gamma ray shielding efficiency of the glasses. The study was conducted using density and molar volume measurements, X-ray diffraction analysis, Fourier transform infrared analysis, non-destructive ultrasonic analysis, and theoretical assessment of the glasses’ gamma ray shielding efficiency using the Phy-X/PSD software. High density values in the range of 5.611–5.735 gcm−3 and the XRD analysis showed no sharp peak indicating the amorphous nature of the glasses. The FTIR spectra revealed the presence of both TeO3 and TeO4 structural units. The values of the elastic moduli microhardness, Debye and softening temperatures, acoustic impedance, diffusion constant, Thermal expansion coefficient and latent heat of melting were studied and discussed among others. Efficiency parameters of radiation shielding such as the coefficients of mass and linear attenuation, effective atomic number, half and tenth value layers, mean free path and effective electron density were calculated theoretically and discussed. Based on the results discussed, the studied MnO2 doped TeO2-PbO-ZnO glasses appeared to be mechanically strong, and thermally stable for radiation shielding applications. Moreso, the glasses appeared to be better in terms of radiation shielding efficiency than commercial concrete materials like serpentine, barite, ferrite, and chromite. © 2024 Elsevier B.V.